Kepercayaan Diri Siswa Melalui Penerapan Metode Role Play : Studi Narrative Inquiry Pada Pembelajaran IPA - Silfia, Fina; Suratno, Tatang; Fatihaturosyidah, Fatihaturosyidah (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Students' self-confidence needs to be owned by students to be able to actualize themselves. Confident students tend to be active in the learning process, while less confident students tend to be passive in the learning process. This study aims to describe the self-confidence of the students of the State Elementary School of Gunungdatar, Cimanuk District, Pandeglang Regency through the role-play learning method and describe the causes of students being confident and not confident. This study uses a qualitative approach with the method of narrative inquiry. The research subjects in this study were sixth-grade students at the State Elementary School of Gunungdatar. The data collection in this research applies observation, interview, and documentation techniques in the form of field notes, inter-research text, and storytelling. The resulting data were analyzed by means of codification and restoration. This research reveals that the things that make students confident are fun and interesting learning situations and things that cause students not to be confident are students do not have confidence in their abilities. When appointed by the teacher and become the center of attention of their friends, it makes them not confident to show their learning abilities. Through the learning process using the role-play method, it can be seen that students begin to dare to express themselves during the learning process, dare to express opinions, dare to ask questions, and respect and correct each other if their friends do something wrong.